Preparation method of two-dimensional semiconductor phase change energy storage master batch
Patent Information
- Application Number
- CN202611111981.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-09-08
AI Technical Summary
该问题的实质在于缺少能够兼顾片层组装、相变限域和树脂相容的连续界面结构
1、采用含邻苯二酚基和氨基的有机界面层对二硫化钼纳米片进行表面功能化,并使其与表面羟基化氮化硼纳米片以面接触方式交替组装,可在两类二维片层之间形成连续界面结合,使所得异质层状骨架在固液分离、浸渍、包覆和熔融混炼过程中保持层间排列。连通片层间隙为熔融脂肪酸相变组分提供连续容纳空间,减压浸渍与恢复常压配合可促使相变组分进入骨架内部,经冷却后形成限域型相变复合颗粒。该结构避免二硫化钼和氮化硼以相互分离的孤立填料形式存在,使二硫化钼片层、氮化硼片层和脂肪酸相变组分在同一颗粒内部保持相邻分布,并减少片层在后续熔融加工中的重新堆叠。面接触排列缩短二硫化钼与氮化硼之间的界面传热距离,连通间隙使热量能够由片层界面传入相变组分,避免热量在孤立填料周围集中。脂肪酸相变组分受到片层间隙和有机界面层共同约束,熔融后沿颗粒外部迁移的通道减少。由此,二维异质层状骨架的面接触关系和连通间隙能够在母粒制备及再加工过程中得到延续,脂肪酸相变组分不再单纯依赖载体树脂黏度或开放孔道固定,从而对应解决二维片层结构难以稳定保持及相变组分难以持续限域的主要技术问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This product relates to the field of nanomaterials and phase change energy storage material preparation technology, and discloses a method for preparing two-dimensional semiconductor phase change energy storage masterbatch. Background Technology
[0002] Phase change energy storage masterbatches typically use phase change materials such as fatty acids, paraffin wax, or polyethylene glycol as the heat storage component, and polyethylene, polypropylene, ethylene-vinyl acetate copolymer, or thermoplastic polyurethane as the carrier resin, and are prepared through melt blending, extrusion, and pelletizing. To reduce the migration of phase change materials from the carrier resin in the molten state, conventional methods often employ adsorption with porous inorganic materials, microencapsulation, or cross-linked polymer confinement. Porous adsorption methods generally involve first mixing expanded graphite, silica, diatomaceous earth, or porous carbon materials with the molten phase change material, allowing the phase change material to enter the pores, and then mixing it with the carrier resin. Microencapsulation methods form a polyurea, acrylic resin, or other polymer shell around the phase change core material, and then disperse the microcapsules in the resin matrix. Cross-linked confinement methods constrain the flow of the phase change component by forming a three-dimensional network. The above technologies can reduce the leakage of phase change materials to a certain extent, but there are usually multiple interfaces between the phase change components and inorganic fillers, coating shells and carrier resins, the heat transfer path is discontinuous, and under high filling conditions, particle agglomeration, increased mixing torque and uneven dispersion in the terminal resin are likely to occur.
[0003] In recent years, two-dimensional semiconductor materials have been used in phase change composites to improve heat input by utilizing their layered structure and photothermal response. Molybdenum disulfide nanosheets can be directly added to molten phase change materials or polymer matrices after liquid-phase exfoliation, or they can be modified with polydopamine, silanes, or polymers before being composited with phase change materials. To compensate for the limited out-of-plane thermal conductivity of molybdenum disulfide, existing methods also incorporate boron nitride nanosheets, graphene, or other two-dimensional thermally conductive fillers, and use high-speed shearing, ultrasonic dispersion, solution mixing, or melt blending to allow different layers to coexist in the composite system. Some methods co-impregnate two-dimensional fillers with fatty acid phase change components onto a porous carrier, or use compatibilizers to improve the interfacial bonding between inorganic layers and polyolefin carriers. Most of these methods are based on the independent dispersion of two two-dimensional materials. There is a lack of stable surface contact assembly relationship between molybdenum disulfide and boron nitride. The sheets are prone to recombination during drying, melt mixing and re-extrusion. The fatty acid phase change components mainly rely on open pores or resin viscosity to maintain their properties, making it difficult to form a continuous structure that simultaneously penetrates the photothermal conversion phase, the thermally conductive phase and the thermally stored phase.
[0004] Therefore, the main technical problem that existing technologies need to solve is: in the preparation of two-dimensional semiconductor phase change energy storage masterbatches, how to construct and maintain a stable heterogeneous layered confined structure formed by molybdenum disulfide nanosheets and boron nitride nanosheets, so that the two types of two-dimensional sheets maintain surface contact arrangement after melt granulation and reprocessing of the final resin, and that the fatty acid phase change component is stably contained within the interconnected interlayer gaps. Existing direct blending methods cannot simultaneously control the interfacial bonding between sheets, the morphology of interlayer pores, and the spatial position of the phase change component. Molybdenum disulfide is prone to interfacial stacking, and boron nitride is prone to forming isolated clusters in the resin, with the heat transfer pathway between them interrupted by processing shear. Furthermore, the open adsorption structure is prone to channel migration after the phase change component melts, leading to separation of the two-dimensional sheets from the phase change component. Simply increasing the amount of inorganic filler will further compress the containment space of the phase change component and exacerbate the interfacial discontinuity within the masterbatch. The essence of this problem lies in the lack of a continuous interfacial structure that can simultaneously achieve sheet assembly, phase change confinement, and resin compatibility. Summary of the Invention
[0005] To address the aforementioned technical problems, this product provides a method for preparing a two-dimensional semiconductor phase change energy storage masterbatch, comprising the following steps: Molybdenum disulfide nanosheets were surface-organically functionalized to form an organic interface layer containing catechol and amino groups on the surface of the molybdenum disulfide nanosheets, thus obtaining functionalized molybdenum disulfide nanosheets. Functionalized molybdenum disulfide nanosheets and surface-hydroxylated boron nitride nanosheets are assembled, and the functionalized molybdenum disulfide nanosheets and surface-hydroxylated boron nitride nanosheets are arranged alternately in a face-contact manner to form a two-dimensional heterogeneous layered framework with interconnected interlayer gaps. The fatty acid phase change component in a molten state is introduced into the interlayer gaps of a two-dimensional heterogeneous layered framework and then cooled and solidified to obtain confined phase change composite particles. Confined phase change composite particles are coated with a vinyl copolymer containing anhydride graft segments to form a compatible coating layer; Confined phase change composite particles with a compatibility coating layer are melt-blended, extruded, and pelletized with a thermoplastic carrier resin to obtain a two-dimensional semiconductor phase change energy storage masterbatch.
[0006] The organic interface layer containing catechol and amino groups formed on the surface of molybdenum disulfide nanosheets possesses polar functional groups, which can alter the original surface state of the molybdenum disulfide nanosheets and form interfacial adsorption and polar interactions when it comes into contact with surface-hydroxylated boron nitride nanosheets. After the molybdenum disulfide nanosheets and surface-hydroxylated boron nitride nanosheets are arranged alternately in a surface contact manner, a continuous interfacial bonding region is formed between adjacent layers, reducing the possibility of the two types of nanosheets stacking into clusters separately. The alternately arranged two-dimensional layers together form a connected interlayer gap. The molten fatty acid phase change component enters the connected interlayer gap in a flowing state and contacts the organic interface layer and the surface of the two-dimensional layers. After cooling, the fatty acid phase change component solidifies within the interlayer gap, forming confined phase change composite particles with a two-dimensional heterogeneous layered framework as the confined carrier. The compatibility coating layer covers the outer surface of the confined phase change composite particles and forms a transition interface between the confined phase change composite particles and the thermoplastic carrier resin during subsequent melt mixing, allowing the particles to be dispersed within the continuous phase formed by the thermoplastic carrier resin. The preparation process sequentially completes the two-dimensional sheet surface conditioning, heterogeneous sheet assembly, molten phase change component introduction, particle interface coating and resin carrier composite, so that molybdenum disulfide nanosheets, surface hydroxylated boron nitride nanosheets and fatty acid phase change components are kept adjacent to each other in the same confined phase change composite particles.
[0007] Furthermore, in the above technical solution, the surface organic functionalization treatment includes: dispersing molybdenum disulfide nanosheets in a weakly alkaline medium containing dopamine, causing dopamine to undergo oxidative self-polymerization on the surface of the molybdenum disulfide nanosheets to form a continuous polydopamine interface layer, and forming an organic interface layer containing catechol groups and amino groups through the polydopamine interface layer.
[0008] In practice, dopamine undergoes oxidation and intermolecular polymerization in a weakly alkaline medium, depositing a polydopamine interface layer on the surface of molybdenum disulfide nanosheets. This polydopamine interface layer is continuously distributed along the surface of the molybdenum disulfide nanosheets, and its catechol and amino groups are retained within the interface layer, providing polar sites for interfacial bonding between the originally chemically limited molybdenum disulfide nanosheets and surface-hydroxylated boron nitride nanosheets. During preparation, the molybdenum disulfide nanosheets are first dispersed in a weakly alkaline medium containing dopamine. Dopamine undergoes oxidative self-polymerization in the dispersed state, and the resulting polydopamine gradually adheres to the surface of the molybdenum disulfide nanosheets, subsequently yielding functionalized molybdenum disulfide nanosheets. The continuous polydopamine interface layer also prevents direct basal contact between adjacent molybdenum disulfide nanosheets, reducing the tight overlap of the nanosheets during subsequent assembly and drying.
[0009] Furthermore, in the above technical solution, the surface-hydroxylated boron nitride nanosheets are prepared by oxidizing and activating boron nitride nanosheets. Functionalized molybdenum disulfide nanosheets and surface-hydroxylated boron nitride nanosheets are sequentially adsorbed, assembled, and separated in a dispersion medium, so that the catechol groups and amino groups in the organic interface layer form an interfacial bonding structure with the hydroxyl groups on the surface of the surface-hydroxylated boron nitride nanosheets.
[0010] In practice, oxidation activation treatment introduces hydroxyl groups onto the surface of boron nitride nanosheets, giving them surface sites capable of polar interaction with the polydopamine interfacial layer. After the functionalized molybdenum disulfide nanosheets and the surface-hydroxylated boron nitride nanosheets are introduced into the same dispersion medium, the catechol groups and amino groups in the organic interfacial layer form interfacial adsorption relationships with the hydroxyl groups in the sheet contact region, transforming the two types of two-dimensional nanosheets from an independently dispersed state to an interconnected assembled state. After adsorption and assembly, solid-liquid separation is performed, allowing the two-dimensional nanosheets with the formed interfacial bonding structure to separate from the dispersion medium and gradually approach each other, thus maintaining the surface contact relationship between the functionalized molybdenum disulfide nanosheets and the surface-hydroxylated boron nitride nanosheets. The interfacial bonding structure is distributed in the heterogeneous sheet contact region, constraining the relative displacement of the sheets during subsequent impregnation and melt mixing.
[0011] Furthermore, in the above technical solution, the fatty acid phase change component is formed by at least two fatty acids with different carbon chain lengths to form a eutectic phase change system. The fatty acid phase change component is mixed with a two-dimensional heterogeneous layered framework in a molten state and enters the interlamellar gaps through a combination of depressurized impregnation and restoration of normal pressure.
[0012] In practice, fatty acids with different carbon chain lengths are mixed to form a eutectic phase transition system. This system is fluid in its molten state and can penetrate the interior of a two-dimensional heterogeneous layered framework. During depressurization impregnation, gas in the interlamellar gaps of the two-dimensional heterogeneous layered framework is expelled, and the molten fatty acid phase transition component contacts the framework and covers its outer surface. Upon restoration to normal pressure, external pressure acts on the molten fatty acid phase transition component, causing it to migrate into the framework along the interlamellar gaps. Because the interlamellar gaps are interconnected, the fatty acid phase transition component can gradually enter the framework from the outside of the particles, rather than merely adhering to the framework surface. After impregnation, cooling is performed, and the fatty acid phase transition component within the interlamellar gaps changes from a molten state to a solid state, remaining between the alternating two-dimensional lamellar layers.
[0013] Furthermore, in the above technical solution, the vinyl copolymer containing anhydride grafted segments is a maleic anhydride-grafted ethylene-vinyl acetate copolymer, and the compatibility coating layer is formed by solution coating or melt coating of confined phase change composite particles with maleic anhydride-grafted ethylene-vinyl acetate copolymer. The thermoplastic carrier resin is selected from at least one of ethylene-vinyl acetate copolymer, polyethylene, polypropylene and thermoplastic polyurethane.
[0014] In practice, the maleic anhydride-grafted ethylene-vinyl acetate copolymer possesses both anhydride grafted segments and ethylene-vinyl acetate copolymer segments. The anhydride grafted segments can form interfacial contact with the polydopamine interface layer on the surface of the confined phase change composite particles, while the ethylene-vinyl acetate copolymer segments can undergo segmental entanglement and interdiffusion with the thermoplastic carrier resin in the molten state. When solution coating is used, the maleic anhydride-grafted ethylene-vinyl acetate copolymer is first distributed on the outer surface of the confined phase change composite particles in a medium, forming a compatible coating layer after the medium is removed. When melt coating is used, the maleic anhydride-grafted ethylene-vinyl acetate copolymer adheres to the outer surface of the confined phase change composite particles in a softened or molten state. When the coated confined phase change composite particles are melt-mixed with the selected thermoplastic carrier resin, the compatible coating layer is located between the particles and the carrier resin and deforms with the flow of the carrier resin, thereby maintaining a continuous coating state on the outer surface of the particles.
[0015] Furthermore, in the above technical solution, before performing surface organic functionalization treatment, the molybdenum disulfide raw material is subjected to liquid phase exfoliation and classification treatment to obtain few-layer molybdenum disulfide nanosheets, and dopamine is directly added to the dispersion system after liquid phase exfoliation to carry out oxidative self-polymerization, so that the polydopamine interface layer simultaneously covers the base surface and edge defect sites of the few-layer molybdenum disulfide nanosheets.
[0016] In practice, liquid-phase exfoliation separates the interlayer structure of molybdenum disulfide raw materials, forming few-layer molybdenum disulfide nanosheets. Grading separates larger particles that are not fully exfoliated from the few-layer molybdenum disulfide nanosheets, ensuring that the molybdenum disulfide nanosheets undergoing subsequent surface organic functionalization treatment have a relatively uniform sheet morphology. After liquid-phase exfoliation, the few-layer molybdenum disulfide nanosheets are not dried; instead, dopamine is directly added to the original dispersion system, reducing the re-stacking of the nanosheets during drying and re-dispersion. During the oxidative self-polymerization of dopamine in the dispersion system, both the basal surface and edge defect sites of the few-layer molybdenum disulfide nanosheets are in contact with the medium, allowing the generated polydopamine to be deposited simultaneously on both the basal surface and edge defect sites. After the edge defect sites are covered by the polydopamine interface layer, the surface chemical state of the few-layer molybdenum disulfide nanosheets tends to be uniform, enabling them to participate in subsequent heterogeneous sheet assembly through the polydopamine interface layer.
[0017] Furthermore, in the above technical solution, the adsorption assembly includes alternately adding functionalized molybdenum disulfide nanosheet dispersion and surface hydroxylated boron nitride nanosheet dispersion to the assembly system, and performing shear dispersion and static adsorption after each addition. After multiple alternating additions, directional filtration or centrifugal compaction is performed to form a two-dimensional heterogeneous layered framework of functionalized molybdenum disulfide nanosheets and surface hydroxylated boron nitride nanosheets stacked alternately.
[0018] In practice, functionalized molybdenum disulfide nanosheet dispersions and surface-hydroxylated boron nitride nanosheet dispersions are added alternately, ensuring that each newly added two-dimensional nanosheet preferentially contacts another type of two-dimensional nanosheet already present in the assembly system. Shear dispersion after each addition distributes the newly added nanosheets throughout the assembly system and reduces local aggregation of similar nanosheets. Subsequent static adsorption allows the functionalized molybdenum disulfide nanosheets and surface-hydroxylated boron nitride nanosheets to form surface contact through the interaction between the organic interface layer and the hydroxyl groups. After multiple alternating additions, the two types of two-dimensional nanosheets are deposited and adsorbed sequentially, forming an alternatingly stacked initial assembly. Directional filtration utilizes the flow and compaction generated when the liquid flows out along the filtration direction to align the two-dimensional nanosheets along their basal plane; centrifugal compaction utilizes centrifugal force to gradually bring the initial assembly closer together and compact it. After directional filtration or centrifugal compaction, adjacent layers remain alternately stacked, while interconnected gaps between the layers are maintained for the molten fatty acid phase change components to enter.
[0019] Furthermore, in the above technical solution, before introducing the fatty acid phase change component into the two-dimensional heterogeneous layered framework, the two-dimensional heterogeneous layered framework is subjected to vacuum degassing treatment. Then, under the condition of keeping the fatty acid phase change component in a molten state, it is subjected to depressurized impregnation, and after stepwise restoration to normal pressure, solid-liquid separation and removal of surface free phase change component, confined phase change composite particles are obtained.
[0020] In practice, vacuum degassing removes gas from the interlamellar gaps of the two-dimensional heterogeneous layered framework, reducing the obstruction of internal gas from the molten fatty acid phase change component entering the interlamellar gaps. The degassed two-dimensional heterogeneous layered framework comes into contact with the molten fatty acid phase change component and remains impregnated under reduced pressure, allowing the fatty acid phase change component to cover the framework surface and the entrance to the interlamellar gaps. Gradually restoring atmospheric pressure slows down pressure changes, allowing the molten fatty acid phase change component to gradually enter the interlamellar gaps as pressure recovers, reducing localized compaction of the framework or uneven distribution of the phase change component caused by rapid restoration of atmospheric pressure. After impregnation, solid-liquid separation is performed to separate the molten fatty acid phase change component that has not entered the two-dimensional heterogeneous layered framework from the impregnated framework. Free phase change component on the particle surface is then removed, ensuring that the fatty acid phase change component in the resulting confined phase change composite particles is mainly distributed within the interlamellar gaps. The confined phase change composite particles are then cooled and proceed to the subsequent coating step.
[0021] Furthermore, in the above technical solution, when using maleic anhydride-grafted ethylene-vinyl acetate copolymer to coat confined phase change composite particles, the maleic anhydride grafted segments are first brought into contact and bonded with the polydopamine interface layer. Then, the confined phase change composite particles forming the initial coating layer are melt-blended with the ethylene-vinyl acetate copolymer carrier resin, so that the initial coating layer and the ethylene-vinyl acetate copolymer carrier resin form a continuous polymer phase.
[0022] In practice, during the coating process, the maleic anhydride grafted segments of the maleic anhydride-grafted ethylene-vinyl acetate copolymer face towards the polydopamine interface layer on the surface of the confined phase change composite particles, forming interfacial contact with the polar groups in the polydopamine interface layer. This allows the maleic anhydride-grafted ethylene-vinyl acetate copolymer to adhere to the outer surface of the particles, forming the initial coating layer. After the confined phase change composite particles with the initial coating layer are added to the plasticized ethylene-vinyl acetate copolymer carrier resin, the ethylene-vinyl acetate copolymer segments in the initial coating layer diffuse and entangle with the carrier resin segments in the molten state. As melt mixing continues, the interface between the initial coating layer and the ethylene-vinyl acetate copolymer carrier resin gradually transitions, forming a continuous polymer phase, in which the confined phase change composite particles remain dispersed.
[0023] Furthermore, in the above technical solution, melt mixing includes sequentially plasticizing the carrier resin, adding confined phase change composite particles with a compatibility coating layer, low-shear dispersion and homogenization mixing, and extrusion and pelletizing are carried out under the condition that the fatty acid phase change component is kept inside the two-dimensional heterogeneous layered skeleton, so that the obtained two-dimensional semiconductor phase change energy storage masterbatch has a continuous phase composed of thermoplastic carrier resin and compatibility-coated confined phase change composite particles dispersed in the continuous phase.
[0024] In practice, during melt mixing, the carrier resin is first plasticized to form a fluid, continuous melt. Then, confined phase change composite particles with a compatibility coating are added to prevent concentrated mechanical compression of the particles before the carrier resin is plasticized. After the particles are added, low-shear dispersion is employed, allowing the compatibility-coated confined phase change composite particles to flow with the carrier resin melt and gradually separate, while reducing excessive shear on the two-dimensional heterogeneous layered skeleton. Following low-shear dispersion, homogenization mixing is performed to ensure a stable distribution of the particles within the thermoplastic carrier resin. During extrusion, the thermoplastic carrier resin, as the continuous phase, carries the compatibility-coated confined phase change composite particles through the extrusion channel. The compatibility coating is located between the particles and the continuous phase, while the two-dimensional heterogeneous layered skeleton is located inside the particles. The fatty acid phase change component is retained within the interconnected interlamellar gaps of the two-dimensional heterogeneous layered skeleton. After pelletizing, the extrudate forms a two-dimensional semiconductor phase change energy storage masterbatch with the thermoplastic carrier resin as the continuous phase and the compatibility-coated confined phase change composite particles as the dispersed phase.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Molybdenum disulfide nanosheets are surface-functionalized using an organic interface layer containing catechol and amino groups. This functionalized layer is then alternately assembled with surface-hydroxylated boron nitride nanosheets in a face-contact manner. This creates a continuous interfacial bond between the two types of two-dimensional sheets, maintaining the interlayer arrangement of the resulting heterogeneous layered framework during solid-liquid separation, impregnation, coating, and melt mixing. The interconnected interlayer gaps provide continuous space for the molten fatty acid phase change component. The combination of reduced pressure impregnation and restoration to normal pressure promotes the entry of the phase change component into the framework, forming confined phase change composite particles after cooling. This structure avoids the isolated filler forms of molybdenum disulfide and boron nitride, ensuring that the molybdenum disulfide sheets, boron nitride sheets, and fatty acid phase change component remain adjacent within the same particle, reducing the re-stacking of sheets during subsequent melt processing. The face-contact arrangement shortens the interfacial heat transfer distance between molybdenum disulfide and boron nitride, while the interconnected gaps allow heat to be transferred from the sheet interface to the phase change component, preventing heat concentration around isolated fillers. The fatty acid phase change component is constrained by both the interlayer gaps and the organic interface layer, reducing the channels for migration along the outside of the particle after melting. Therefore, the surface contact relationships and interconnected gaps of the two-dimensional heterogeneous layered framework can be maintained during masterbatch preparation and reprocessing. The fatty acid phase change component no longer relies solely on the viscosity of the carrier resin or open channels for fixation, thus addressing the main technical problems of the difficulty in maintaining the stable two-dimensional layered structure and the difficulty in continuously confining the phase change component.
[0026] 2. Forming a vinyl copolymer coating layer containing anhydride-grafted segments on the confined phase change composite particles allows the coating layer to bond with the polydopamine interfacial layer. This facilitates the formation of a continuous polymer phase during compounding with carrier resins such as ethylene-vinyl acetate copolymer, polyethylene, polypropylene, or thermoplastic polyurethane, reducing interfacial separation between the inorganic composite particles and the carrier resin. The coated particles are added after the carrier resin has been plasticized, and low-shear dispersion and homogenization mixing are employed to reduce breakage of the heterogeneous layered skeleton during extrusion, ensuring the fatty acid phase change components remain within the interlayer gaps. Liquid-phase exfoliation and classification of the molybdenum disulfide raw material, along with covering its basal surface and edge defects with the polydopamine interfacial layer, improves the consistency of the surface state of different layers. Hydroxylation treatment of boron nitride nanosheets, followed by alternating addition, shear dispersion, static adsorption, and directional filtration or centrifugal compaction to form an alternating stacked structure, further stabilizes the skeleton pore distribution and layer contact relationships. Vacuum degassing, reduced pressure impregnation, gradual restoration to atmospheric pressure, and removal of surface free phase change components work together to reduce residual air gaps within the framework and free fatty acids on the particle surface, thus reducing the possibility of particle adhesion after pelleting and surface precipitation during reprocessing. These treatments collectively reduce debinding, segregation, and secondary agglomeration of phase change composite particles in the continuous phase of the masterbatch, ensuring that the masterbatch maintains a relatively uniform particle distribution and layered structure even after remelting. Detailed Implementation
[0027] The present invention will be further described in detail below with reference to embodiments. Those skilled in the art can reproduce the technical solution of the present invention and achieve its claimed technical effects based on the content disclosed in this specification. It should be noted that the following embodiments are only used to explain the present invention and are not intended to limit the scope of protection of the present invention. Any non-substantial improvements and adjustments made based on the core concept of the present invention should fall within the scope of protection of the present invention.
[0028] Example 1: This example prepares a two-dimensional semiconductor phase change energy storage masterbatch. By mass, the raw materials include 3.0 parts of molybdenum disulfide nanosheets, 7.0 parts of boron nitride nanosheets, 0.5 parts of dopamine, 37.5 parts of lauric acid, 12.5 parts of stearic acid, 8.0 parts of maleic anhydride-grafted ethylene-vinyl acetate copolymer, and 31.5 parts of ethylene-vinyl acetate copolymer.
[0029] The specific preparation method is as follows: Step 1: Add molybdenum disulfide raw material to deionized water at a mass ratio of 1:100. Treat at a shear rate of 6000 rpm for 30 minutes, followed by ultrasonic exfoliation at a power of 500 watts for 2 hours. After exfoliation, centrifuge at 2500 times gravity acceleration for 10 minutes to remove the incompletely exfoliated sediment, retaining the upper dispersion containing few-layer molybdenum disulfide nanosheets. Adjust the solid content of the dispersion to 5 g / L and adjust it to a weakly alkaline pH of 8.5. Add dopamine and stir at 25°C for 12 hours to allow dopamine to undergo oxidative self-polymerization on the surface of the few-layer molybdenum disulfide nanosheets, forming a continuous polydopamine interface layer. After the reaction, perform solid-liquid separation and wash three times with deionized water. Redisperse the obtained solids in deionized water to prepare a functionalized molybdenum disulfide nanosheet dispersion with a solid content of 5 g / L.
[0030] Step 2: Add boron nitride nanosheets to deionized water at a mass ratio of 1:50 and disperse at a shear rate of 3000 rpm for 20 minutes. Place the resulting dispersion in a closed oxygen-containing environment and perform hydrothermal oxidation activation treatment at 180°C for 6 hours to form hydroxyl groups on the surface of the boron nitride nanosheets. After cooling to room temperature, perform solid-liquid separation, wash three times with deionized water, and redisperse in deionized water to prepare a dispersion of surface-hydroxylated boron nitride nanosheets with a solid content of 5 g / L.
[0031] Step 3: Divide the functionalized molybdenum disulfide nanosheet dispersion and the surface-hydroxylated boron nitride nanosheet dispersion into 6 equal portions each; add the first portion of functionalized molybdenum disulfide nanosheet dispersion to the assembly container, treat it at a shear rate of 3000 rpm for 10 minutes, and allow it to stand for 20 minutes for adsorption. Then add the first portion of surface-hydroxylated boron nitride nanosheet dispersion, treat it under the same shear conditions for 10 minutes, and allow it to stand for 20 minutes for adsorption. Continue to add the remaining dispersions alternately in the above order, and perform shear dispersion and stand for adsorption after each addition. After all the dispersions have been added, continue to stand for 1 hour to allow the catechol groups and amino groups in the polydopamine interface layer to form an interfacial bonding structure with the hydroxyl groups on the surface of the surface-hydroxylated boron nitride nanosheets.
[0032] Step four involves directional filtration of the dispersible system after adsorption and assembly. The absolute pressure during filtration is 20 kPa, which gradually compacts the functionalized molybdenum disulfide nanosheets and the surface-hydroxylated boron nitride nanosheets along the filtration direction while maintaining their surface contact arrangement. The solid obtained from filtration is then vacuum-dried at 50°C for 12 hours, followed by crushing and sieving to obtain a two-dimensional heterogeneous layered framework with a particle size of 150–300 micrometers and interconnected interlamellar gaps.
[0033] Step 5: Add lauric acid and stearic acid to a molten container and stir at 80°C for 30 minutes to form a homogeneous fatty acid eutectic phase transition system. Preheat the two-dimensional heterolayered framework to 75°C and perform vacuum degassing at an absolute pressure of 5 kPa for 30 minutes. Add the molten fatty acid phase transition component to the two-dimensional heterolayered framework and impregnate under reduced pressure at an absolute pressure of 8 kPa for 30 minutes. After the reduced pressure impregnation is completed, restore the system pressure to 20 kPa, 40 kPa, 60 kPa, 80 kPa and atmospheric pressure in sequence, maintaining each pressure stage for 5 minutes, and continue to maintain at atmospheric pressure for 20 minutes to allow the molten fatty acid phase transition component to enter the interlamellar gaps of the two-dimensional heterolayered framework.
[0034] Step 6: The impregnation system is subjected to solid-liquid separation at 60°C and centrifuged at 1500 rpm for 5 minutes to remove the surface free phase change components that have not entered the interlayer gaps; the obtained particles are cooled to 25°C to solidify the fatty acid phase change components in the interlayer gaps, thus obtaining confined phase change composite particles.
[0035] Step 7: Add maleic anhydride-grafted ethylene-vinyl acetate copolymer to a melt mixing device and plasticize for 5 minutes at 95°C and 30 rpm; add confined phase change composite particles and mix for 10 minutes at 40 rpm to allow the maleic anhydride grafted segments to contact and bond with the polydopamine interface layer on the surface of the confined phase change composite particles, and to allow the ethylene-vinyl acetate copolymer segments to cover the outer surface of the particles; after mixing, cool to room temperature to obtain confined phase change composite particles with a compatibility coating layer.
[0036] Step 8: Add the ethylene-vinyl acetate copolymer to the melt mixing equipment and plasticize it for 5 minutes at 105°C and 50 rpm; add the confined phase change composite particles with a compatibility coating layer and disperse them under low shear at 60 rpm for 8 minutes, then homogenize and mix them for 5 minutes at 40 rpm; feed the mixture into the extrusion equipment, with the temperature ranges of the extrusion equipment set to 95°C, 105°C, 110°C and 105°C respectively, and the screw speed at 60 rpm; cool and pelletize the extrudate to obtain two-dimensional semiconductor phase change energy storage masterbatch with a particle size of 2-4 mm.
[0037] Example 2: The difference between this example and Example 1 is that the amount of molybdenum disulfide nanosheets is adjusted to 4.0 parts and the amount of boron nitride nanosheets is adjusted to 6.0 parts, so that the total amount of both is kept at 10.0 parts; the amount of dopamine, lauric acid, stearic acid, maleic anhydride grafted ethylene-vinyl acetate copolymer and ethylene-vinyl acetate copolymer and all preparation process conditions are the same as in Example 1.
[0038] Functionalized molybdenum disulfide nanosheet dispersions and surface-hydroxylated boron nitride nanosheet dispersions were prepared according to the steps in Example 1. Two-dimensional heterogeneous layered frameworks were formed by alternating addition, shear dispersion, static adsorption and directional filtration. Subsequently, the fatty acid phase change components were impregnated under reduced pressure, coated with compatibility, melt-mixed, extruded and pelletized to obtain two-dimensional semiconductor phase change energy storage masterbatch.
[0039] Example 3: The difference between this example and Example 1 is that the amount of molybdenum disulfide nanosheets is adjusted to 2.0 parts and the amount of boron nitride nanosheets is adjusted to 8.0 parts, so that the total amount of both is kept at 10.0 parts; the amount of other raw materials and the preparation process conditions are the same as in Example 1.
[0040] In this embodiment, the liquid phase exfoliation, surface organic functionalization treatment, oxidation activation treatment, adsorption assembly, directional filtration, vacuum degassing, reduced pressure impregnation, compatibility coating and melt granulation are completed according to the preparation sequence of Example 1 to obtain a two-dimensional semiconductor phase change energy storage masterbatch.
[0041] Example 4: The difference between this example and Example 1 is that the fatty acid phase change component is composed of 35.0 parts of lauric acid and 15.0 parts of stearic acid, so that the total amount of fatty acid phase change component is kept at 50.0 parts; the amount of other raw materials and the preparation process conditions are the same as in Example 1.
[0042] Lauric acid and stearic acid were stirred at 80°C for 30 minutes to form a fatty acid eutectic phase transition system. Subsequently, the system was introduced into the interlamellar gaps of a two-dimensional heterogeneous layered framework in accordance with the vacuum degassing, reduced pressure impregnation and gradual restoration to normal pressure method of Example 1. The remaining steps were the same as in Example 1.
[0043] Example 5: The difference between this example and Example 1 is that the fatty acid phase change component is composed of 40.0 parts of lauric acid and 10.0 parts of stearic acid, so that the total amount of fatty acid phase change component is kept at 50.0 parts; the amount of other raw materials and the preparation process conditions are the same as in Example 1.
[0044] This embodiment uses the same two-dimensional heterogeneous layered framework preparation conditions, reduced pressure impregnation conditions, compatibility coating conditions, and melt mixing conditions as in Example 1 to obtain a two-dimensional semiconductor phase change energy storage masterbatch.
[0045] Example 6: The difference between this example and Example 1 is that the amount of maleic anhydride-grafted ethylene-vinyl acetate copolymer is adjusted to 6.0 parts, and the amount of ethylene-vinyl acetate copolymer is adjusted to 33.5 parts, so that the total amount of raw materials remains unchanged; the amount of other raw materials and the preparation process conditions are the same as in Example 1.
[0046] After obtaining the confined phase change composite particles, 6.0 parts of maleic anhydride-grafted ethylene-vinyl acetate copolymer were plasticized at 95°C and melt-coated onto the confined phase change composite particles. Subsequently, the particles were melt-blended with 33.5 parts of ethylene-vinyl acetate copolymer. The remaining operations were the same as in Example 1.
[0047] Example 7: The difference between this example and Example 1 is that the amount of maleic anhydride-grafted ethylene-vinyl acetate copolymer is adjusted to 10.0 parts, and the amount of ethylene-vinyl acetate copolymer is adjusted to 29.5 parts, so that the total amount of raw materials remains unchanged; the amount of other raw materials and the preparation process conditions are the same as in Example 1.
[0048] After obtaining the confined phase change composite particles, 10.0 parts of maleic anhydride-grafted ethylene-vinyl acetate copolymer were plasticized at 95°C and melt-coated onto the confined phase change composite particles. Subsequently, the particles were melt-blended with 29.5 parts of ethylene-vinyl acetate copolymer. The remaining operations were the same as in Example 1.
[0049] Example 8: This example keeps the raw material composition and amount of each raw material unchanged from Example 1, only the dopamine oxidation self-polymerization time is adjusted from 12 hours to 8 hours, and the other conditions are the same as in Example 1.
[0050] Specifically, the solid content of the few-layer molybdenum disulfide nanosheet dispersion was maintained at 5 g / L, the pH of the weakly alkaline medium was maintained at 8.5, and the oxidative self-polymerization temperature was maintained at 25°C. After 8 hours of dopamine reaction, solid-liquid separation and washing were performed to obtain functionalized molybdenum disulfide nanosheets. Subsequently, the preparation, adsorption assembly, directional filtration, vacuum impregnation, compatibility coating, melt mixing, extrusion, and pelletizing of surface-hydroxylated boron nitride nanosheets were completed according to Example 1.
[0051] Example 9: This example keeps the raw material composition and amount of each raw material unchanged from Example 1. The only difference is that the absolute pressure of the fatty acid phase change component during vacuum impregnation is adjusted from 8 kPa to 15 kPa. The vacuum impregnation time is still 30 minutes. All other conditions are the same as in Example 1.
[0052] After the two-dimensional heterogeneous layered framework was vacuum degassed for 30 minutes under an absolute pressure of 5 kPa, it was mixed with the fatty acid phase change component in a molten state and impregnated for 30 minutes under an absolute pressure of 15 kPa. Subsequently, the pressure was restored stepwise in the order of 20 kPa, 40 kPa, 60 kPa, 80 kPa and atmospheric pressure. The remaining steps were the same as in Example 1.
[0053] Comparative Example 1: This comparative example is a comparative example of surface-deficient hydroxylated boron nitride nanosheets.
[0054] In this comparative example, 7.0 parts of boron nitride nanosheets were removed from Example 1, and the amount of ethylene-vinyl acetate copolymer was adjusted from 31.5 parts to 38.5 parts, keeping the total amount of raw materials unchanged. The amounts of the remaining raw materials were the same as in Example 1.
[0055] The molybdenum disulfide raw material was subjected to liquid phase exfoliation, classification, and polydopamine interface coating according to Example 1. The resulting functionalized molybdenum disulfide nanosheets were no longer alternately adsorbed and assembled with surface hydroxylated boron nitride nanosheets, but were directly formed into a molybdenum disulfide sheet framework through directional filtration. Subsequently, vacuum degassing, reduced pressure impregnation of fatty acid phase change components, removal of surface free phase change components, compatibility coating, melt mixing, extrusion, and pelletizing were completed according to Example 1, with the remaining conditions being the same as in Example 1.
[0056] Comparative Example 2: This comparative example uses a conventional direct melt blending process, and the types and amounts of raw materials are the same as in Example 1.
[0057] Lauric acid and stearic acid were melt-mixed at 80°C for 30 minutes to obtain a fatty acid phase change component. Ethylene-vinyl acetate copolymer and maleic anhydride-grafted ethylene-vinyl acetate copolymer were plasticized at 105°C, and molybdenum disulfide nanosheets without surface organic functionalization treatment, boron nitride nanosheets without oxidation activation treatment, and the molten fatty acid phase change component were added sequentially. The mixture was mixed at 60 rpm for 13 minutes. The mixture was extruded and pelletized according to the extrusion temperature and screw speed of Example 1.
[0058] This comparative example does not perform organic functionalization treatment on the surface of molybdenum disulfide nanosheets, does not perform hydroxylation treatment on the surface of boron nitride nanosheets, does not perform alternating adsorption assembly of the two types of two-dimensional nanosheets, does not perform reduced pressure impregnation of fatty acid phase change components, and does not pre-form a compatible coating layer. The remaining extrusion and pelletizing conditions are the same as in Example 1.
[0059] Comparative Example 3: This comparative example is a comparative example where the melt mixing shear conditions deviate from the low shear range. The raw material composition, the amount of each raw material, and all process conditions before forming the compatible encapsulated phase change composite particles are the same as in Example 1.
[0060] After plasticizing the ethylene-vinyl acetate copolymer at 105°C and 50 rpm for 5 minutes, confined phase change composite particles with a compatibility coating were added. The rotation speed during the dispersion stage was adjusted from 60 rpm in Example 1 to 250 rpm, and the dispersion time was maintained at 8 minutes. Then, homogenization, mixing, extrusion and pelletizing were carried out according to Example 1, with the remaining conditions the same as in Example 1.
[0061] Test method: 1. Sample preparation Two-dimensional semiconductor phase change energy storage masterbatches obtained in Examples 1-9 and Comparative Examples 1-3 were processed under the same drying conditions and then hot-pressed at 120°C to obtain circular test samples with a diameter of 50 mm and a thickness of 2 mm. Five parallel samples were prepared for each group, and the average value of the test results was taken.
[0062] 2. Thermal conductivity test The transient plane heat source method was used to test the thermal conductivity of each sample at 25℃. Before the test, the samples were equilibrated in a 25℃ environment for 24 hours. Three different locations were selected for testing each sample, and the average value of the measured values at each location was taken as the thermal conductivity of the sample.
[0063] 3. Photothermal conversion efficiency test The samples were continuously irradiated under a light source with an intensity of 1000 W / m² for 20 minutes. The change in sample surface temperature over time was recorded, and the photothermal conversion efficiency was calculated based on sample mass, specific heat, phase change heat absorption, and incident energy. The irradiation distance, irradiation area, and ambient temperature of each sample were kept consistent.
[0064] 4. Melt Leakage Rate Test Weigh samples of equal mass, place them on pre-weighed absorbent paper, and keep them at 90°C for 2 hours. After cooling, weigh the samples and absorbent paper separately, and calculate the melt leakage rate based on the amount of sample mass reduction.
[0065] 5. Phase transition enthalpy and cycle retention rate test The initial phase transition enthalpy of the sample was determined by differential scanning calorimetry, with a heating range of 20–90 °C and a constant heating and cooling rate. Subsequently, the sample was subjected to 500 melt-crystallization cycles between 20 °C and 90 °C, and the phase transition enthalpy was measured again. The retention rate of the phase transition enthalpy after the cycles relative to the initial phase transition enthalpy was calculated.
[0066] 6. Aggregation Area Ratio Test Each sample was fractured at low temperature, and 10 observation areas with the same area were selected from the fracture surface for microscopic observation. The two-dimensional nanosheets with continuous size greater than 20 micrometers were identified as agglomeration areas, and the proportion of the agglomeration area to the total observation area was calculated by image analysis.
[0067] 7. Surface temperature difference test The sample was irradiated for 10 minutes under the same lighting conditions as the photothermal conversion efficiency test. The highest and lowest temperatures on the sample surface were recorded using infrared thermal imaging, and the difference between the two was taken as the maximum surface temperature difference.
[0068] The test results are shown in Table 1.
[0069]
[0070] Example 1 exhibits a thermal conductivity of 1.38 W / (m·K), a photothermal conversion efficiency of 89.1%, a melt leakage rate of 0.62%, a phase change enthalpy retention rate of 94.6% after 500 cycles, an agglomeration area ratio of 1.9%, and a maximum surface temperature difference of 2.8 °C. These results indicate that functionalized molybdenum disulfide nanosheets and surface-hydroxylated boron nitride nanosheets, arranged in alternating surface contacts, maintain continuous lamellar contact within the confined phase change composite particles. The molten fatty acid phase change component, after vacuum degassing, reduced pressure impregnation, and gradual restoration to atmospheric pressure, enters the interconnected lamellar gaps. Furthermore, a compatible coating layer is formed on the outside of the particles by maleic anhydride-grafted ethylene-vinyl acetate copolymer, ensuring that thermal conductivity, photothermal conversion, phase change confinement, and resin dispersion are in a mutually synergistic state.
[0071] In Example 2, the amount of molybdenum disulfide nanosheets was increased from 3.0 parts to 4.0 parts, while the amount of boron nitride nanosheets was correspondingly reduced. The photothermal conversion efficiency increased to 91.8%, but the thermal conductivity decreased to 1.31 W / (m·K), and the maximum surface temperature difference increased to 3.1 °C. This change indicates that increasing the proportion of molybdenum disulfide nanosheets can increase the photothermal conversion interface, but decreasing the proportion of boron nitride nanosheets correspondingly reduces the lateral heat diffusion capacity within the two-dimensional heterogeneous layered framework.
[0072] In Example 3, increasing the proportion of surface-hydroxylated boron nitride nanosheets resulted in a thermal conductivity of 1.48 W / (m·K) and a maximum surface temperature difference of 2.5 °C, but the photothermal conversion efficiency decreased to 84.0%. The comparison between Examples 2 and 3 indicates that molybdenum disulfide nanosheets and boron nitride nanosheets undertake different interfacial heat transfer processes, and changes in their ratio lead to corresponding changes in photothermal conversion efficiency and heat diffusion capacity. Example 1 achieved a more balanced result between the two indicators.
[0073] In Examples 4 and 5, the mass ratio of lauric acid to stearic acid was varied, resulting in initial phase transition enthalpies of 85.5 J / g and 87.2 J / g, respectively. After 500 cycles, the enthalpy retention rate of the phase transition was higher than 93%, and the melt leakage rate was lower than 0.7%. These results indicate that, under the condition of a constant total amount of fatty acid phase transition components, a two-dimensional heterolayered framework can be applied to fatty acid eutectic phase transition systems with different compositions. The change in the ratio of lauric acid to stearic acid mainly affects the initial phase transition enthalpy, with relatively little impact on lamellar confinement and cycle stability.
[0074] In Example 6, reducing the amount of maleic anhydride-grafted ethylene-vinyl acetate copolymer to 6.0 parts resulted in an increase in melt leakage rate to 1.18%, an increase in agglomeration area ratio to 3.7%, and a decrease in phase change enthalpy retention rate after 500 cycles to 91.5%. Reducing the amount of the compatibility coating layer decreased the continuity of the coating on the outer surface of the confined phase change composite particles, reduced the interfacial transition region between the particles and the continuous phase of the ethylene-vinyl acetate copolymer, and led to more localized interfacial separation during melt processing and cycling.
[0075] In Example 7, increasing the amount of maleic anhydride-grafted ethylene-vinyl acetate copolymer to 10.0 parts reduced the melt leakage rate to 0.46%, the agglomeration area ratio to 1.5%, and the phase change enthalpy retention rate after 500 cycles to 95.1%. Due to the increased mass proportion of the compatibility coating layer in the masterbatch, the relative mass proportion of the fatty acid phase change component was diluted, and the initial phase change enthalpy decreased to 84.9 J / g. The results of Examples 6 and 7 indicate that the amount of compatibility coating layer can regulate the relationship between particle interface stability and heat storage per unit mass.
[0076] In Example 8, shortening the dopamine oxidative self-polymerization time to 8 hours resulted in a decrease in thermal conductivity to 1.30 W / (m·K), an increase in the agglomeration area ratio to 3.1%, and an increase in the maximum surface temperature difference to 3.8 °C. Under otherwise identical conditions, shortening the oxidative self-polymerization time reduced the continuity of the polydopamine interface layer, decreased the interfacial bonding area between the functionalized molybdenum disulfide nanosheets and the surface-hydroxylated boron nitride nanosheets, and made the two-dimensional heterolayered framework more susceptible to localized lamellar displacement during subsequent processing.
[0077] In Example 9, after adjusting the absolute pressure of the vacuum impregnation to 15 kPa, the initial phase change enthalpy was 85.8 J / g, the melt leakage rate was 0.78%, and the phase change enthalpy retention rate after 500 cycles was 93.1%. Compared with Example 1, the higher impregnation pressure reduced the pressure difference between the interlaminar gaps and the outside, and the degree to which the fatty acid phase change components entered the skeleton decreased. However, the resulting masterbatch still maintained a low leakage rate and a high cycle retention rate, indicating that the preparation method can still form confined phase change composite particles when the vacuum impregnation conditions change.
[0078] In Comparative Example 1, after removing the surface-hydroxylated boron nitride nanosheets, the photothermal conversion efficiency remained at 88.9%, but the thermal conductivity decreased to 0.67 W / (m·K), the maximum surface temperature difference increased to 8.6 °C, the melt leakage rate increased to 2.85%, and the phase transition enthalpy retention rate after 500 cycles decreased to 82.4%. These results indicate that molybdenum disulfide nanosheets can retain photothermal conversion capabilities, but the layered framework formed solely by functionalized molybdenum disulfide nanosheets lacks the heterogeneous surface contact pathways formed by boron nitride nanosheets. Heat tends to concentrate in localized areas, and the structural stability of the interlayer gaps and the degree of restriction on fatty acid phase transition components decrease simultaneously.
[0079] Although Comparative Example 2 used the same raw material composition as Example 1, it did not form a polydopamine interface layer, surface-hydroxylated boron nitride nanosheets, a two-dimensional heterogeneous layered framework, or a compatible coating layer. Its thermal conductivity was only 0.74 W / (m·K), melt leakage rate reached 5.92%, agglomeration area ratio reached 13.4%, and phase change enthalpy retention rate after 500 cycles was 73.8%. In the direct melt blending process, molybdenum disulfide nanosheets and boron nitride nanosheets were stacked separately, and the fatty acid phase change component was mainly distributed between the carrier resin and the inorganic layers, lacking confinement to connect the interlayer gaps. This comparison demonstrates that simple blending of the same components cannot achieve the comprehensive properties formed in Example 1.
[0080] Comparative Example 3 only increased the rotation speed of the low-shear dispersion stage from 60 rpm to 250 rpm. The melt leakage rate increased from 0.62% in Example 1 to 3.48%, the agglomeration area ratio increased to 6.3%, and the phase change enthalpy retention rate after 500 cycles decreased to 81.7%. High shear conditions caused some two-dimensional heterogeneous layered skeletons to break down, and discontinuous regions were generated in the compatibility coating layer outside the confined phase change composite particles. The fatty acid phase change components in the original interconnected interlayer gaps were more likely to migrate to the continuous phase of the carrier resin in the molten state.
[0081] A comparison of Example 1 and Comparative Example 1 shows that the surface contact assembly between surface-hydroxylated boron nitride nanosheets and functionalized molybdenum disulfide nanosheets can simultaneously alter heat diffusion and the confinement state of phase transition. A comparison of Example 1 and Comparative Example 2 shows that the performance difference does not stem from the type or total amount of raw materials, but rather from the continuous technical relationship formed by surface organic functionalization, surface hydroxylation, alternating adsorption assembly, reduced pressure impregnation, and compatibility coating. A comparison of Example 1 and Comparative Example 3 shows that low shear dispersion is a necessary process condition for maintaining the integrity of the two-dimensional heterogeneous layered framework and the compatibility-coated confined phase transition composite particles. With the combined effect of these techniques, the resulting masterbatch simultaneously maintains a high thermal conductivity, high photothermal conversion efficiency, low melt leakage rate, high cyclic phase transition enthalpy retention rate, and low agglomeration area ratio. This combined result cannot be achieved independently by any single component among the molybdenum disulfide nanosheets, boron nitride nanosheets, fatty acid phase transition components, or compatibilizer.
Claims
1. A method for preparing a two-dimensional semiconductor phase change energy storage masterbatch, characterized in that, Includes the following steps: Molybdenum disulfide nanosheets are surface-functionalized with organic compounds to form an organic interface layer containing catechol and amino groups on the surface of the molybdenum disulfide nanosheets, resulting in functionalized molybdenum disulfide nanosheets. These functionalized molybdenum disulfide nanosheets are then assembled with surface-hydroxylated boron nitride nanosheets, arranging them alternately in a face-contact manner to form a two-dimensional heterogeneous layered framework with interconnected interlayer gaps. Molten fatty acid phase change components are introduced into the interconnected interlayer gaps of the two-dimensional heterogeneous layered framework, and then cooled and solidified to obtain confined phase change composite particles. The confined phase change composite particles are then coated with a vinyl copolymer containing anhydride graft segments to form a compatible coating layer. Finally, the confined phase change composite particles with the compatible coating layer are melt-blended with a thermoplastic carrier resin, extruded, and pelletized to obtain a two-dimensional semiconductor phase change energy storage masterbatch.
2. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 1, characterized in that, The surface organic functionalization treatment includes: dispersing the molybdenum disulfide nanosheets in a weakly alkaline medium containing dopamine, causing the dopamine to undergo oxidative self-polymerization on the surface of the molybdenum disulfide nanosheets to form a continuous polydopamine interface layer, and constituting the organic interface layer containing catechol groups and amino groups through the polydopamine interface layer.
3. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 1, characterized in that, The surface-hydroxylated boron nitride nanosheets are prepared by oxidative activation treatment of boron nitride nanosheets. The functionalized molybdenum disulfide nanosheets and the surface-hydroxylated boron nitride nanosheets are sequentially adsorbed, assembled, and separated in a dispersion medium, so that the catechol groups and amino groups in the organic interface layer form an interfacial bonding structure with the hydroxyl groups on the surface of the surface-hydroxylated boron nitride nanosheets.
4. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 1, characterized in that, The fatty acid phase change component is a eutectic phase change system formed by at least two fatty acids with different carbon chain lengths. The fatty acid phase change component is mixed with the two-dimensional heterogeneous layered framework in the molten state and enters the interlayer gaps of the connected layers by a combination of depressurized impregnation and restoration of normal pressure.
5. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 2, characterized in that, The vinyl copolymer containing anhydride-grafted segments is a maleic anhydride-grafted ethylene-vinyl acetate copolymer. The compatibility coating layer is formed by solution coating or melt coating the confined phase change composite particles with the maleic anhydride-grafted ethylene-vinyl acetate copolymer. The thermoplastic carrier resin is selected from at least one of ethylene-vinyl acetate copolymer, polyethylene, polypropylene, and thermoplastic polyurethane.
6. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 2, characterized in that, Before performing the surface organic functionalization treatment, the molybdenum disulfide raw material is subjected to liquid phase exfoliation and classification to obtain few-layer molybdenum disulfide nanosheets. Dopamine is then directly added to the dispersion system after liquid phase exfoliation to carry out oxidative self-polymerization, so that the polydopamine interface layer simultaneously covers the basal surface and edge defect sites of the few-layer molybdenum disulfide nanosheets.
7. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 3, characterized in that, The adsorption assembly includes alternately adding functionalized molybdenum disulfide nanosheet dispersion and surface-hydroxylated boron nitride nanosheet dispersion into the assembly system, and performing shear dispersion and static adsorption after each addition. After multiple alternating additions, directional filtration or centrifugal compaction is performed to form the two-dimensional heterogeneous layered framework in which the functionalized molybdenum disulfide nanosheets and the surface-hydroxylated boron nitride nanosheets are alternately stacked.
8. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 4, characterized in that, Before introducing the fatty acid phase change component into the two-dimensional heterogeneous layered framework, the two-dimensional heterogeneous layered framework is subjected to vacuum degassing. Then, the reduced pressure impregnation is performed while keeping the fatty acid phase change component in a molten state. After stepwise restoration to normal pressure, solid-liquid separation and removal of surface free phase change components, the confined phase change composite particles are obtained.
9. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 5, characterized in that, When the maleic anhydride-grafted ethylene-vinyl acetate copolymer is used to coat the confined phase change composite particles, the maleic anhydride grafted segments are first brought into contact with the polydopamine interface layer, and then the confined phase change composite particles forming the initial coating layer are melt-blended with the ethylene-vinyl acetate copolymer carrier resin, so that the initial coating layer and the ethylene-vinyl acetate copolymer carrier resin form a continuous polymer phase.
10. The method for preparing two-dimensional semiconductor phase change energy storage masterbatch according to claim 1, characterized in that, The melt mixing includes sequentially plasticizing the thermoplastic carrier resin, adding the confined phase change composite particles with the compatibility coating layer, low-shear dispersion, and homogenization mixing. The extrusion and pelletizing are carried out under the condition that the fatty acid phase change component is kept inside the two-dimensional heterogeneous layered framework, so that the resulting two-dimensional semiconductor phase change energy storage masterbatch has a continuous phase composed of the thermoplastic carrier resin and compatibility-coated confined phase change composite particles dispersed in the continuous phase.